Foraging Habitat Distributions Affect Territory Size and Shape in the Tuamotu Kingfisher - Kesler, Dylan C. (International Journal of Zoology, 2012)
I studied factors influencing territory configuration in the Tuamotu kingfisher (Todiramphus gambieri). Radiotelemetry data were used to define territory boundaries, and I tested for effects on territory size and shape of landscape habitat composition and foraging patch configuration. Tuamotu kingfisher territories were larger in areas with reduced densities of coconut plantation foraging habitat, and territories were less circular in the study site that had a single slender patch of foraging habitat. Maximum territory length did not differ between study sites, however, which suggested that the size of Tuamotu kingfisher territories might be bounded by the combined influence of maximum travel distances and habitat configurations. Results also suggested that birds enlarge territories as they age. Together, results supported previous work indicating that territory configurations represent a balance between the costs of defending a territory and gains from territory ownership.